Implementation of Sustainable Tourism Promotion through Natural and Cultural Tourism Documentation in Tuapeijat, Mentawai Islands - Asnur, Lise; Nabilah, Lutfa Rana; Sitompul, Hotnur Fadila; Rano, Delfi Christopel; Sahid, Alimin; Saufari, Shizany (Universitas Pahlawan Tuanku Tambusai, 2025)
This article aims to describe the implementation of sustainable tourism promotion through the documentation of natural and cultural tourism in Tuapeijat Village, North Sipora District, Mentawai Islands Regency. The activity was carried out as part of the Padang State University's Community Service Program (KKN), focusing on tourism potential, including Awera Beach, Berkat Beach, Putoutogat Island, mangrove ecotourism with traditional toek cuisine, and the cultural attraction of sago worm consumption. The method used was a descriptive qualitative approach with data collection techniques in the form of field observations, visual documentation, and brief interviews with tourism actors and the local community. The results of the activity showed that tourism documentation was able to increase public awareness of the importance of preserving nature and local culture, while also serving as an effective promotional medium for the development of sustainable tourism. The conclusion of this study is that tourism promotion based on documentation can be a synergistic strategy between environmental conservation, community economic empowerment, and the introduction of Mentawai culture.